Modernizing Madrasah Learning in the Era of Digital Technology (A Conceptual Perspective of Learning Dynamics in Madrasahs as Islamic Education Institutions): Modernisasi Pembelajaran Madrasah Di Era Teknologi Digital (Perspektif Konseptual Dinamika Pembelajaran di Madrasah sebagai Institusi Pendidikan Islam) - Nadlif, Ainun; Farihah, Anis (Universitas Muhammadiyah Sidoarjo, 2024)
Improving the quality of learning in Madrasahs is a strategic and constructive step that is expected to bring Islamic education to be more adaptive in the era of digital technology. The dynamics in the world of realistic learning demand good and conducive interactions between teachers and learners. Madrasahs, as educational institutions, require greater attention from the community. Individualist behavior that ignores social demoralization can threaten morality if Madrasahs remain neutral to social values. The moral decline in society, especially among teenagers, emphasizes the importance of value-based character learning. A learning environment based on trust, care, and respect can enhance motivation, creativity, and affective and cognitive development. Role models from educators and reinforcement of character values are essential for shaping learners' character. Islamic education in Madrasahs has contributed greatly to the history of national education. The Indonesian government, based on Pancasila and the 1945 Constitution, guarantees the implementation of Islamic education and provides freedom for Muslims to develop.